EVALUASI PELAKSANAAN PENDIDIKAN BERBASIS MASYARAKAT PADA PKBM HANGTUAH DAN PKBM SARI - Sri Pudjiastuti; Rr. Sri Kartikowati; Nurpit Junus (Universitas Riau, 2019)
The focus of this research is the implementation of community-based education (PBM) in PKBM Hangtuah and PKBM Sari with research subfokus: (1) Understanding of institution leadership on PBM; (2) Implementation of planning process, organizing, leading and controlling curriculum in PKBM studied; (3) The way of institution leadership in ensuring all PKBM learning activities to be run in accordance with the work program (running a smooth ship). This research uses a qualitative approach where researchers describe the phenomena obtained during the research on the implementation of PBM in PKBM studied. Data collection techniques used include (1) interviews, (2) observation, (3) documentation study. As for techniques to check the validity of the data using triangulation data. Data analysis techniques using data reduction, data presentation, verification or conclusion. The conclusion of this study are (1) Understanding PKBM leaders Hangtuah and PKBM Sari pertained good to PBM. The leaders of both institutions understand the concept of PKBM established from, by and for the community, knowing operational guidelines for the implementation of PKBM and has conducted the management of PKBM in accordance with the technical guidelines, knowing the technical service program and the obligations of PKBM and knowing the community needs around PKBM; (2) The leaders of both institutions have done a good planning, organizing, leading and controlling process. In the process of planning, the leaders of both institutions have set goals but do not include all the existing stakeholders, have institutional development strategies, although they are incomplete, and have job descriptions and schedule of PKBM activities. In the organizing process, both leaders of PKBM institutions have been managing in accordance with their vision and mission, determining strategies and targets that include the outcome criteria, quality and time constraints even though the document on this matter is not fully owned, and holds an internal meeting of the agency to carry out the review this is not done routinely. In the process of controlling, the leaders of both institutions often control the activities of the agencies in the field, often check the conditions in the field and explore information about the course of an activity to know the weaknesses and mistakes in the field, directly reprimand and make corrections to the mistakes that occur and provide input and warning to tutors and residents learn. (3) The leaders of both institutions have ensured that all learning activities work well through observation and direct action to the field and by communicating with staff, study residents and tutors consistently from time to time, rarely assessing tutors or teachers, assessment is done, it is well documented, has supervision in the academic field but this is not done regularly or consistently, PKBM Hangtuah leadership has conducted supervision in the field of lifeskills consistently by joining the field during the event held, while the leadership PKBM Sari do not do it consistently.